Search for the production of single vector-like and excited quarks in the Wt final state in pp collisions at √s = 8 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2016)
A search for vector-like quarks and excited quarks in events containing a top quark and a W boson in the final state is reported here. The search is based on 20.3 fb−1 of proton-proton collision data taken at the LHC at a centre-of-mass energy of 8 TeV recorded by the ATLAS detector. Events with one or two leptons, and one, two or three jets are selected with the additional requirement that at least one jet contains a b-quark. Single-lepton events are also required to contain at least one large-radius jet from the hadronic decay of a high-pTW boson or a top quark. No significant excess over the expected background is observed and upper limits on the cross-section times branching ratio for different vector-like quark and excited-quark model masses are derived. For the excited-quark production and decay to Wt with unit couplings, quarks with masses below 1500 GeV are excluded and coupling-dependent limits are set.